WNT-conditioned mechanism of exit from postchemotherapy shock of differentiated tumour cells - Tsydenova, Irina A.; Dolgasheva, Daria S.; Gaptulbarova, Kseniya A.; Ibragimova, Marina K.; Tsyganov, Matvey M.; Kravtsova, Ekaterina A.; Nushtaeva, Anna A.; Litvyakov, Nicolay V. (Cancers)
Metastatic disease is the leading cause of death in cancer patients. In our earlier clinical study of breast cancer patients, it was shown that metastasis after neoadjuvant chemotherapy and adjuvant hormone therapy occurred only in patients with WNT signalling in the tumour due to activator gene amplifications (15 genes identified) and/or negative regulator gene deletions (7 genes identified) of WNT signalling pathway genes. If, on the contrary, activator deletions and negative regulator amplifications are noted, these patients do not metastasise. We hypothesized that spontaneous exit of tumour cells from postchemotherapy shock (replication arrest, senescence) is associated with ectopic expression of WNT signalling pathway genes due to activator amplifications and negative regulator deletions. In the present work, we have confirmed this assumption on cell cultures.